Improving Sales Performance: A Case Study In A Korean Based Adhesive Company - Low, Chie Chong (2014)
This case study is to explore the business issues that concerns Best Chemical’s sales performance in Malaysia. The analysis methods are complex because they are not merely focused on the corporate strategy level, but also involve Korea’s culture and preferred business style. Established in 2007, Best Chemical Co., Ltd. is a Korean based adhesive company servicing semiconductor and electronics industry. In 2009, they appointed Advance Resources Sdn. Bhd. as their distributor. Their global business portrayed limited achievement for the past four years. In fact, their distributor was not able to achieve the target of 72 sales cases and the sales closing rate was also far below 20% of the closing rate target set by Best Chemical.